EDUCAÇÃO PÚBLICA E DESENVOLVIMENTO: UM ESTUDO SOBRE O ENSINO FUNDAMENTAL PÚBLICO NO MUNICÍPIO DE PONTA GROSSA/PR - Bueno, Josenilda Aparecida Ribas (2017)
This research aims to discuss the relationship between public education and development, analyzing the relationship between public education policy and social inequality. For this purpose, public primary education in the municipality of Ponta Grossa/PR, from 1991 to 2015, was delimited as a field of analysis. The justification for the choice of Ponta Grossa/PR is due to the fact that although the municipality represents the largest source of education in the Campos Gerais region, its IDEB has been lower, especially in the initial years of elementary education, than in other municipalities of similar size, such as Cascavel, Londrina and Maringá. The temporal delimitation is due to the promulgation of the Federal Constitution of 1988, which made possible new paths for the Brazilian educational policy. Thus, guided by the social-developmental conception that permeates this work and by the assumptions of the welfare state, we seek to describe and discuss the offer of public elementary education in Ponta Grossa/PR in its main aspects, as well as the importance of Educational investments for the development of the municipality. The methodological approach is based on qualitative research and the procedure adopted in data collection was the combination of bibliographical and documentary research. As for the structure, the work has five chapters; The first and second seek to analyze development from the perspective of the welfare state, as well as the relationship between public education and development; The third chapter is about addressing the main changes in educational policy after the 1988 Constitution; The fourth chapter presents some of the main aspects of the offer of elementary education in Ponta Grossa/PR and; Finally, the fifth chapter seeks to analyze the evolution of the educational profile of municipal workers, evaluating possible effects of education on the salaries of workers in the period. Among the main results, the research evidenced a substantial change in the educational profile of the workforce in the municipality, which in part seems to have contributed to the increases in workers' income in the analyzed period. The data also provided subsidies so that some aspects of Ponta Grossa public primary education could be identified